The Lack of Transparency in Procurement of Goods in Village Governments in Indonesia: an Examples in Rangkah Kidul Village, Sidoarjo - Afnia Nur Masjidah; Rifqi Ridho Phahlevy; Emy Rosnawati (Indonesian Journal of Law and Economics Review, 2018)
The principle of Good Governance contains Transparency, which is transparent and Accountability which explains that the procurement of goods and services in the Village needs to be regulated in a regulation that can guarantee legal certainty and produce goods and goods that are qualified. There were many different interpretations in each region which resulted in the vulnerability of misuse of rules, methods, to the determination of winners at a smaller level, one of them was in the Village Alert Operational Car Procurement in Rangkah Kidul Village, Sidoarjo. In the research, the procurement of Village Alert Operational Cars in Rangkah Kidul Sidoarjo Village used normative followed by case studies that looked at and observed the procurement. In fact the procurement is not based on the principle of openness and accountability. Besides that in nominal prices, accountability to the Rangkah Kidul village government in Sidoarjo is not worthy of being said as a good village government because it is not appropriate in the application of the General Principles of Good / Decent Governance.